The Nursing Student: An Agent of Change - Luz Enith Velásquez Restrepo; Doris León Mejía; Marta Lucía Gallón Ochoa (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nursing students, in their training and internships, play a crucial role as an agent of change in the community, since beyond acquiring clinical skills, they are involved in community projects that allow them to have a positive impact on public health, PHC, health education and disease prevention. Therefore, this article examines how nursing students contribute to the well-being of the community, driving significant changes in the quality of life, their role has evolved significantly, highlighting the acquisition of clinical skills, but also as a transformative actor within communities, their training and active participation in community projects, contribute to the well-being of the community, allowing us to analyse their potential to influence social transformation and the creation of healthy environments, demonstrating their ability to lead change initiatives and their impact on improving quality of life.